2019
DOI: 10.1016/j.neuropsychologia.2019.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Landmark Task as a tool for studying hemispheric specialization: What's really right?

Abstract: The "Landmark Task" (LT) is a line bisection judgment task that predominantly activates right parietal cortex. The typical version requires observers to judge bisections for horizontal lines that cross their egocentric midline and therefore may depend on spatial attention as well as spatial representation of the line segments. To ask whether the LT is indeed right-lateralized regardless of spatial attention (for which the right hemisphere is known to be important), we examined LT activation in 26 neurologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Seydell-Greenwald and colleagues (2019) examined neurologically healthy young adults using the landmark test with vertical instead of horizontal stimuli. These investigators found right-lateralized parietal activations similar to those reported in other landmark tests with horizontal lines [18].…”
Section: Introductionsupporting
confidence: 81%
“…Seydell-Greenwald and colleagues (2019) examined neurologically healthy young adults using the landmark test with vertical instead of horizontal stimuli. These investigators found right-lateralized parietal activations similar to those reported in other landmark tests with horizontal lines [18].…”
Section: Introductionsupporting
confidence: 81%
“…Importantly, we do not intend to suggest that all visual‐spatial functions start out with a bilateral pattern of activation early in life and remain this way throughout development. Indeed, studies assessing the lateralization of other spatial tasks in adults, such as line bisection, suggest that the right hemisphere plays a predominant role, with little involvement of the left (Cavézian et al, 2012; Çiçek et al, 2009; Fink et al, 2000; Seydell‐Greenwald et al, 2019). It is notable, however, that the “puzzle game” used in the present study is based on the block construction task, which is one of the most widely used instruments to evaluate spatial abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Third, as reviewed by Seydell‐Greenwald et al. (2019), using a vertical line presented at screen center minimizes activations associated with shifts in spatial attention to left or right hemispace, which could influence lateralization of activation patterns (Corbetta et al., 1993; Corbetta & Shulman, 2011; Heilman & van den Abell, 1980; Mesulam, 1981). Thus, we are able to isolate right‐lateralized activation associated with the spatial computations involved in comparison of relative length and proportion, without also drawing in activation that may be associated with left/right shifts in attention.…”
Section: Methodsmentioning
confidence: 99%
“…First, as reviewed above, it has been shown that this task elicits robust right‐lateralized parietal activation, regardless of whether the stimulus lines are presented in vertical or horizontal orientations (Fink et al., 2001). Second, we aimed to build upon the findings of a previous study of adults (Seydell‐Greenwald et al., 2019), which also used vertical lines. Third, as reviewed by Seydell‐Greenwald et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation